Iminoboronates as useful scaffolds for tumor-targeting - Santos, Fábio Miguel Figueiredo 1987- (2021)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2018